Stem Cell Research - Panno, Joseph (New York, NY, 2005)
Examines stem cells from the scientific and social viewpoints, including what they are, their laboratory study, their use in medicine, the ethical issues involved, and the legal issues in American and Europe.
Stem cells are not all equal -- Human stem cells -- Medical applications -- Commercialization of human stem cells -- Reality check -- The ethics of stem cell research -- Legal issues -- Resource center.
Includes bibliographical references (p. 157-161) and index.
Keywords: Medical ethics; Cells; Medicine; Research